Assessing Interobserver Agreement (IOA) with Procedural Integrity: Evaluation of Training Methods among Classroom Instructors. Issue 1 (2nd January 2021) - Hartz, Renee M.; Gould, Kaitlin; Harper, Jill M.; Luiselli, James K.
Abstract: This study evaluated training methods to improve procedural integrity of classroom instructorswhen assessing interobserver agreement (IOA) with their students. Compared to baseline conditions in a multiple baseline across settings design, training that included a memo-task analysis review did not improve procedural integrity. Subsequent intervention consisting of single-session group administered behavioral skills training (BST: instruction, demonstration, role-playing, performance feedback) increased and stabilized procedural integrity of all instructors. These findings support previous training research concerned with procedural integrity of care providers and a competency-based approach towards improving IOA assessment.